High-Zinc Supplementation of Weaned Piglets Affects Frequencies of Virulence and Bacteriocin Associated Genes Among Intestinal Escherichia coli Populations - Johanns, Vanessa C.; Epping, Lennard; Semmler, Torsten; Ghazisaeedi, Fereshteh; Lübke-Becker, Antina; Pfeifer, Yvonne; Eichhorn, Inga; Merle, Roswitha; Bethe, Astrid; Walther, Birgit; Wieler, Lothar H. (Frontiers in Veterinary Science, 2020)
To prevent economic losses due to post-weaning diarrhea (PWD) in industrial pig production, zinc (Zn) feed additives have been widely used, especially since awareness has risen that the regular application of antibiotics promotes buildup of antimicrobial resistance in both commensal and pathogenic bacteria. In a previous study on 179 Escherichia coli collected from piglets sacrificed at the end of a Zn feeding trial, including isolates obtained from animals of a high-zinc fed group (HZG) and a corresponding control group (CG), we found that the isolate collection exhibited three different levels of tolerance towards zinc, i.e. the minimal inhibitory concentration (MIC) detected was 128, followed by 256 and 512 µg/ml ZnCl2. We further provided evidence that enhanced zinc tolerance in porcine intestinal E. coli populations is clearly linked to excessive zinc feeding. Here we provide insights about the genomic make-up and phylogenetic background of these 179 E. coli genomes. Bayesian analysis of the population structure (BAPS) revealed a lack of association between the actual zinc tolerance level and a particular phylogenetic E. coli cluster or even branch for both, isolates belonging to the HZG and CG. In addition, detection rates for genes and operons associated with virulence (VAG) and bacteriocins (BAG) were lower in isolates originating from the HZG (41% vs. 65% and 22% vs. 35%, p<0.001 and p=0.002, resp.). Strikingly, E. coli harboring genes defining distinct pathotypes associated with intestinal disease, i.e. enterotoxigenic, enteropathogenic and Shiga toxin-producing E. coli (ETEC, EPEC and STEC) constituted 1% of the isolates belonging to the HZG but 14% of those from the CG. Notably, these pathotypes were positively associated with enhanced zinc tolerance (512 µg/ml ZnCl2 MIC, p<0.001). Taken together, zinc excess seems to influence carriage rates of VAGs and BAGs in porcine intestinal E. coli populations, and high-zinc feeding is negatively correlated with enteral pathotype occurrences, which might explain earlier observations concerning the relative increase of Enterobacterales considering the overall intestinal microbiota of piglets during zinc feeding trials while PWD rates have decreased.